THE COST PRINCIPLE. - Staub, Walter A. (The Accounting Review, 1942)
In considering the cost section of the statement of accounting principles underlying corporate financial statements, which was issued by the American Accounting Association in June 1941, the author assumes it is the wish of those who arranged the program for this session that he speaks from the standpoint of the practicing accountant rather than deal with the subject from the viewpoint of pure theory. It may seem trite, but nevertheless necessary for the record, to point out that cost is one of those words which sounds as though it were a very simple concept, but which proves to be anything but simple in many of situations in which cost must be determined or applied. When cost is to be determined for goods which have been sold, the practical questions which arise in a business with modern production methods and with a variety of products and a highly departmentalized manufacturing organization obviously makes the determination of the cost of sales, a process which inherently rests on many different assumptions and sometimes only intelligent guesses.